2020
DOI: 10.3390/app10228309
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the Chemical and Thermal Behavior of Recycling Agglomerates from EAF by-Products

Abstract: In addition to the blast furnace converter route, electric steel production in the electric arc furnace (EAF) is one of the two main production routes for crude steel. In 2019, the global share of crude steel produced via the electric steel route was 28%, which in numbers is 517 million metric tons of crude steel. The production and processing of steel leads to the output of a variety of by-products, such as dusts, fines, sludges and scales. At the moment, 10–67% of these by-products are landfilled and not rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 12 publications
0
13
0
1
Order By: Relevance
“…The combustion behavior of the briquettes was investigated through the analysis of off-gases, and it was concluded that the CO formation rate was relatively high in biochar briquettes. Willms et al [44] conducted pilot-scale trials using direct current electric arc furnace with a volume of 45 L to assess the dissolution behavior of briquettes in melt pool by chemically analyzing changes taking place in slag and steel melt phases. Takano et al [45] evaluated the metallic yield of briquettes by charging 1 kg of agglomerates into a 2.8 kg of Fe-C liquid melted and kept at 1500 C and then weighing the metal after solidification.…”
Section: Melting Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…The combustion behavior of the briquettes was investigated through the analysis of off-gases, and it was concluded that the CO formation rate was relatively high in biochar briquettes. Willms et al [44] conducted pilot-scale trials using direct current electric arc furnace with a volume of 45 L to assess the dissolution behavior of briquettes in melt pool by chemically analyzing changes taking place in slag and steel melt phases. Takano et al [45] evaluated the metallic yield of briquettes by charging 1 kg of agglomerates into a 2.8 kg of Fe-C liquid melted and kept at 1500 C and then weighing the metal after solidification.…”
Section: Melting Behaviormentioning
confidence: 99%
“…At a preprocessing stage, as-received side stream materials were crushed and sieved if necessary to obtain a particle size that is less than 4 mm, a size which was empirically decided. [44] As-received ladle slag_1, for example, contained large chunks that were not suitable for particle size distribution (PSD) analysis. To determine PSD of the material, two techniques were used.…”
Section: Side Streamsmentioning
confidence: 99%
“…The reductor batch is treated at temperatures above 1200 • C. The diffusion of oxygen from the reaction atmosphere into the material bed is limited by air flow control. Coke and CO (from partial oxidation of carbon) reduce zinc oxide and zinc ferrite to zinc metal [8,[11][12][13][14][15]. Zinc enters the gas phase and is oxidised in the gas stream to ZnO, which is collected on bag filters.…”
Section: Introductionmentioning
confidence: 99%
“…The life cycle analysis of the electric arc furnace slags was performed with the software SimaPro. Additionally, the physical, chemical [ 30 ] and mechanical tests established by the regulations for materials that conform the bituminous mixtures were carried out. The results reflected a clear reduction in the environmental impact by using this industrial by-product, as well as the presence of physical, chemical and mechanical properties suitable for using it in bituminous mixtures.…”
Section: Introductionmentioning
confidence: 99%